DEVELOPMENT OF AN INTEGRATED SCIENCE E-LKPD BASED ON THE GUIDED INQUIRY ON TEMPERATURE AND HEAD MATERIAL FOR GRADE VII OF SMP/MTS - Sari, Desi Permata; Yurnetti, Yurnetti (Department of Science Education, 2025)
This research purpose to produce an integrated science e-LKPD based on guided inquiry on temperature and heat material for class VII SMP/MTs. The researchtype used is research an development (R&D) with a plomp development model. The prototype was generated through a validity test by three validators, namely three science education FMIPA UNP. The practicality test was conducted on two science teachers and students at SMPN 1 Padang Ganting. The results of the assessment for the e-LKPD validity test obtained a value of 0,78 in the category was valid, while the practicality test by the teacher obtained a value of 1,00 in the category was very practical, and the test of practicality by students obtained a value of 0,90 in the category was very practical.